2022
DOI: 10.7554/elife.76479
|View full text |Cite
|
Sign up to set email alerts
|

Transversal functional connectivity and scene-specific processing in the human entorhinal-hippocampal circuitry

Abstract: Scene and object information reach the entorhinal-hippocampal circuitry in partly segregated cortical processing streams. Converging evidence suggests that such information-specific streams organize the cortical - entorhinal interaction and the circuitry's inner communication along the transversal axis of hippocampal subiculum and CA1. Here, we leveraged ultra-high field functional imaging and advance Maass, Berron et al. (2015) who report two functional routes segregating the entorhinal cortex (EC) and the su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…For example, the anterior medial clusters of high endpoint density observed in this study appear to extend across the distal subiculum and proximal presubiculum and lateral clusters appear to extend across the proximal subiculum and distal CA1. This mirrors recent observations in the functional literature that suggest functional clusters also extend across classically defined subfield boundaries ( Dalton et al, 2019a ; Grande et al, 2022 ). Indeed, more fine-grained segmentation can reveal that results, initially attributed to a specific subfield, may actually be driven by a specific subportion within that subfield ( Dalton et al, 2019a ).…”
Section: Discussionsupporting
confidence: 88%
“…For example, the anterior medial clusters of high endpoint density observed in this study appear to extend across the distal subiculum and proximal presubiculum and lateral clusters appear to extend across the proximal subiculum and distal CA1. This mirrors recent observations in the functional literature that suggest functional clusters also extend across classically defined subfield boundaries ( Dalton et al, 2019a ; Grande et al, 2022 ). Indeed, more fine-grained segmentation can reveal that results, initially attributed to a specific subfield, may actually be driven by a specific subportion within that subfield ( Dalton et al, 2019a ).…”
Section: Discussionsupporting
confidence: 88%
“…Extending this work to human data, a recent study from Dalton et al (2022) applied tract density mapping to diffusion MRI data, and found that areas of high tract endpoint density tended to extend across classical subfield boundaries (e.g., across the distal subiculum-proximal presubiculum border, and across proximal subiculum and distal CA1 border). This finding also resonates with functional connectivity studies that show long- and transverse-axis gradients of scene selectivity, not only within entorhinal cortex, but also subicular complex (Grande et al, 2022; Maass et al, 2015; Navarro Schröder et al, 2015; see also Schultz, Sommer & Peters, 2015). Overall, therefore, scene selectivity is likely to be distributed across, and vary within, the borders of cytoarchitecturally defined subfields – a pattern that anatomically-defined subfield ROI-based analyses cannot capture without drawing arbitrary sub-divisions (e.g., splitting subicular complex into medial and lateral components in Hodgetts et al, 2017).…”
Section: Introductionsupporting
confidence: 86%
“…Extending this work to human data, a recent study from Dalton et al (2022) applied tract density mapping to diffusion MRI data, and found that areas of high tract endpoint density tended to extend across classical subfield boundaries (e.g., across the distal subiculumproximal presubiculum border, and across proximal subiculum and distal CA1 border). This finding also resonates with functional connectivity studies that show long-and transverse-axis gradients of scene selectivity, not only within entorhinal cortex, but also subicular complex (Grande et al, 2022;Maass et al, 2015;Navarro Schröder et al, 2015; see also Schultz, Sommer & Peters, 2015 ).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Note however, that our results could be influenced by the low number of seed regions used. Connectivity from the EC to even more brain regions should be investigated to more accurately map the topography of connections, as different regions might be structurally and/or functionally connected with distinct subparts of MEC and LEC (Grande et al, 2022; Witter and Amaral, 2021; Witter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%